Strategi Guru Dalam Meningkatkan Kemampuan Baca Tulis Al-Qur’an Pada Peserta Didik Tunarungu (Studi Kasus di SLBN 1 Kota Pasuruan) - Iwantoro; Nora Niswatul Jannah (JDP (JURNAL DINAMIKA PENDIDIKAN), 2025)
This study aims to describe the teachers' strategies in teaching Qur'anic. Reading and writingand to identify the learning outcomes of deaf student at SLBN 1 Pasuruan City. The research employed a qualitative approach with a case study design. The study was conducted al SLBN 1 Pasuruan City, utilizing both primary and secondary data sources. Data were collected through interviews, observations, and documentation. The data analysis followed the stage of data reduction, data presentation, and drawing and verifying conclutions. To ensure the validity of the findings, the researcher used the data triangulation technique. the result of the study indicate that the teachers' strategies in teaching BTQ to deaf student are quite varied, yet share a common feature in the use of visual media. One of the media used in Hijriyah letter cards, which proved effective in improving the  Qur'anic reading and writing skills of deaf student. The learning outcomes of deaf student in BTQ instruction include: (a) the ability to pronounce letters with fairly accurate articulation and to practice and identify Hijaiyah letters using sign language in accordance with the Indonesia Sign System (SIBI); (b) the ability to understand BTQ learning materials; (c) the ability to answer evaluation questions and daily assignment; and (d)the ability to read and write Hijaiyah letters adequately. In conclusion, the implementation of visual-based learning strategies, particularly the use of Hijaiyah letter cards, effectively enhances the qur'anic literacy skills of deaf student at SLBN 1 Pasuruan City.